Analysis of Determinants that Affect the Attitude of Brides-To-Be to Conduct Hiv Examinations in Palembang City - Sukarni Setya Yuningsih; Arsita Zahara; Putri Julianti; Reza Purnama; Sarah Andiami; Tri Wahyuni (Postgraduate, University of Mataram, 2025)
Premarital HIV testing plays a crucial role in preventing HIV transmission within families. Knowing one’s HIV status before marriage allows couples to take preventive measures—such as consistent condom use—to minimize the risk of transmission through sexual contact. This study aimed to analyze the determinants that influence the attitudes of brides-to-be toward undergoing HIV testing in Palembang City, focusing on respondent characteristics, HIV education, and confidence in being free from HIV infection. This research employed a cross-sectional design involving all prospective brides and grooms in Palembang City. The study was conducted from November 2024 to January 2025 at several health facilities, including PMB Dewi Ratna Sari Am.Keb, PMB Meli Rosita, Citra Maternity Clinic, the South Sumatra Police Polyclinic, and Pendopo Empat Lawing Health Center. Primary data were collected using a structured questionnaire. Data were analyzed using chi-square statistical tests with univariate and bivariate approaches, supported by SPSS version 25. The findings showed no significant relationship between respondent characteristics and attitudes toward HIV testing. However, a significant relationship was found between education about HIV testing and respondents’ confidence in being free from HIV infection with their willingness to undergo HIV testing. This indicates that increasing knowledge and awareness regarding HIV prevention can foster more positive attitudes toward premarital HIV testing. Strengthening HIV education among prospective brides and grooms is essential to encourage proactive attitudes toward testing. Health workers and related institutions are advised to conduct regular educational activities—such as seminars, counseling sessions, and community-based interactive discussions—focused on HIV prevention and early detection.